Ethno-medicinal plants of indigenous people: A case study in Khatling valley of Western Himalaya, India - Hussain, Jaffer; Mehta, J.P.; Singh, Ankit; Bagria, Ajendra Singh; Singh, Hardeep; Nautiyal, M.C.; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2023)
Background: Khatling valley is an unexplored and remote region located in the Uttarakhand state of Indian Himalaya, the area possesses rich medicinal flora, and local inhabitants using these plants since generations. The majority of primary health care depends upon traditional medicine due to the unavailability of a modern medicinal facility, however, the identity of medicinal plants is limited to traditional healers or elder people in the region thus the documentation of such important medicinal knowledge is a dire need for sustainable use. Methods: An ethnomedicinal survey was carried out in this region from 2018 to 2020. Ethnomedicinal data were collected from 82 informants through semi-structured questionnaires and group conversations. To check the popular and frequently used species URs and Informant consensus factor (ICF) were calculated for the collected data. Results: The present study recorded 68 plants from 63 genera and 35 families utilized for treating various disorders. The dominant families were Asteraceae (7) and Rosaceae (6) followed by Apiaceae, Lamiaceae, Ranunculaceae, Polygonaceae, Zingiberiaceae (4 species each). The majority of the useful plants were herbaceous (78%) followed by trees (12%), shrubs (9%), and climbers were the least in number (1%). Most of the plant parts used were leaves and roots 25% each, followed by rhizome, aerial part and tuber (9% each), seeds, fruits, and whole plant (5% each), bark (4%) while, stem, flower, resin, and the bulb has less proportion (1% each). Five drug formulations were used by the local inhabitants of which paste was the most common (32%) followed by powder (31%), decoction (19%), raw (12%), and juice (6%). Some important medicinal plants based on use reports (URs) were Valeriana jatamansi Jones (300 URs and 5 uses), Aconitum lethale Griff. (275 URs and 5 uses), Nardostachys jatamansi (D. Don) DC (250 URs and 4 uses), Solanum nigrum (L.) (234 URs and 5 uses), Paeonia emodi Royle (230 URs and 4 uses). ICF values ranged between 0.96 and 1. The highest ICF value (1) was recorded for mental disorders (ICD code F) and epilepsy (ICD code G) while a minimum of 0.96 was recorded for blood problems (ICD code I). Conclusion: Ethnomedicinal plants having high URs and ICF can be a good source for novel phytoconstituents and novel drug discoveries, apart from this documentation of traditional knowledge will be helpful for the new generation, researchers, and policymakers for sustainable use of the species. Keywords: Ethnomedicine; Indigenous knowledge; Medicinal plants; Remote region